A case of primary amenorrhea with swyer syndrome - Pritti K Priya; Vineet V Mishra; Sumesh Choudhary; Jamal S Rizvi (Wolters Kluwer Medknow Publications, 2017)
Swyer syndrome with complete gonadal dysgenesis is associated with an absence of testicular differentiation in a phenotypic female with a 46, XY karyotype. A 14-year-old unmarried girl was referred with complaints of primary amenorrhea and nondevelopment of breast. Her built was normal. Examination of her secondary sexual characteristics revealed no breast development, absent axillary hairs, and sparse pubic hairs. External genitalia was of female type. Karyotype showed genotype of 46, XY. Magnetic resonance imaging revealed hypoplastic uterus with absent fallopian tubes and ovaries. A diagnosis of Swyer syndrome was made. Laparoscopy showed infantile uterus, normal fallopian tubes, and streak gonads. Laparoscopic removal of streak gonads was done as there is a risk of gonadoblastoma in such cases. The patient was started on hormonal replacement therapy. Swyer syndrome results mainly due to mutation in certain genes such as SRY gene, which leads to failure of development of testis.